1999
DOI: 10.3904/kjim.1999.14.1.85
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pancytopenia Secondary to Low - Dose Pulse Methotrexate Therapy in a Patient with Rheumatoid Arthritis and Renal Insufficiency

Abstract: Most reports on serious MTX toxicity have focused on hepatic abnormalities, while other effects, including hematologic reactions, have not been emphasized. We experienced a case of pancytopenia secondary to MTX therapy in a patient with RA and renal insufficiency. A 67-year-old woman with a 12-year history of active seropositive RA that was a response to non-steroidal anti-inflammatory drugs, hydroxychloroquinine and intra-articular steroid injections, had been followed up and was diagnosed as early chronic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In a previous study, oral mucositis was reported in patients who were prescribed low-dose MTX but ultimately overdosed either due to prescription error or patients' confusion regarding its once-weekly regime. 11,12) In this case study, however, MTX toxicity seems to have been elevated by several factors such as deficiency of FA, 13) reduced renal function, 14) and drug interaction, 13) even if the dosage of MTX does not change. In addition, while oral mucositis has commonly been known to appear as an initial sign of MTX toxicity, it actually develops relatively late after longterm MTX administration in our cases.…”
Section: Discussionmentioning
confidence: 64%
“…In a previous study, oral mucositis was reported in patients who were prescribed low-dose MTX but ultimately overdosed either due to prescription error or patients' confusion regarding its once-weekly regime. 11,12) In this case study, however, MTX toxicity seems to have been elevated by several factors such as deficiency of FA, 13) reduced renal function, 14) and drug interaction, 13) even if the dosage of MTX does not change. In addition, while oral mucositis has commonly been known to appear as an initial sign of MTX toxicity, it actually develops relatively late after longterm MTX administration in our cases.…”
Section: Discussionmentioning
confidence: 64%
“…Chronic kidney disease by itself, not necessarily confined to those with ESRD, seems to predispose patients to the development of this serious complication. 13 Other risk factors reported for pancytopenia with low-dose methotrexate therapy included hypoalbuminemia, advanced age, low serum folate level, elevated mean corpuscular volume, concurrent use of NSAIDs, and concurrent medication with more than 5 drugs. 14 -16 According to a large case series of methotrexate-related pancytopenia, hypoalbuminemia, polypharmacy, advanced age, and renal insufficiency were the most common risk factors, whereas the methotrexate dose was the most predictive of pancytopenia severity.…”
Section: Discussionmentioning
confidence: 98%